2012
DOI: 10.1016/j.clinbiomech.2012.06.013
|View full text |Cite
|
Sign up to set email alerts
|

The pattern of tibial nerve excursion with active ankle dorsiflexion is different in older people with diabetes mellitus

Abstract: Background The peripheral nervous system has an inherent capability to tolerate the gliding (excursion), stretching (increased strain), and compression associated with limb motions necessary for functional activities. The biomechanical properties during joint movements are well studied but the influence of other factors such as limb pre-positioning, age and the effects of diabetes mellitus are not well established for the lower extremity. The purposes of this pilot study were to compare the impact of two diffe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
33
0
1

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 31 publications
(37 citation statements)
references
References 26 publications
2
33
0
1
Order By: Relevance
“…The mechanical properties of peripheral nerves have been extensively examined in animal models Millesi et al, 1995), human cadaver studies (Boyd et al, 2013;Coppieters et al, 2006) and human in vivo studies (Boyd et al, 2012;Ellis et al, 2012). The majority of in vivo studies used ultrasound imaging to quantify nerve excursion and morphology (e.g., cross sectional area) (Beekman and Visser, 2004;Dilley et al, 2001;Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of peripheral nerves have been extensively examined in animal models Millesi et al, 1995), human cadaver studies (Boyd et al, 2013;Coppieters et al, 2006) and human in vivo studies (Boyd et al, 2012;Ellis et al, 2012). The majority of in vivo studies used ultrasound imaging to quantify nerve excursion and morphology (e.g., cross sectional area) (Beekman and Visser, 2004;Dilley et al, 2001;Silva et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The depth of the sciatic nerve in the posterior thigh varied between 3 and 6 mm, and the quality of the nerve image also tended to reduce with increasing age. In addition, substantially larger longitudinal excursion was evoked by the knee movements performed in the present study, compared to Boyd et al (2012) where the ankle was moved. Thus larger amounts of longitudinal nerve excursion with accompanying greater transverse plane motion, and distortion in some cases made it more technically challenging to capture a clear image.…”
Section: Transverse Plane Motionmentioning
confidence: 56%
“…Whilst Boyd et al (2012) has found the centroid method to be reliable, this may be because the tibial nerve is more superficial at both the posterior knee and medial ankle, which results in a better resolution of images. The depth of the sciatic nerve in the posterior thigh varied between 3 and 6 mm, and the quality of the nerve image also tended to reduce with increasing age.…”
Section: Transverse Plane Motionmentioning
confidence: 94%
“…Flexing the hip produces a threefold reduction in the amount of longitudinal tibial nerve movement during ankle dorsiflexion (Boyd et al., ). This finding supports the premise that positioning the body limb in a manner that increases the preloading on the nervous system diminishes the nerve excursion capacity during limb movement.…”
Section: Discussionmentioning
confidence: 99%